Perception of job satisfaction and organizational commitment in improving employee performance - Maarif, Husnul; Japroni, Japroni; Fitria, Yeni; Haryadi, Didit (Junal Ilmu Manajemen, 2024)
Effective management's role is to consider the importance of human resources. Employee performance is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with a population of 70 respondents drawn into a sample using non-probability sampling with saturated sampling / total sampling method. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that job satisfaction significantly affects employee performance. The second hypothesis states that organizational commitment significantly affects employee performance. The third hypothesis states that employee performance is influenced by job satisfaction and organizational commitment, which can simultaneously improve employee performance. Increasing employee performance, which is the cause of job satisfaction and commitment, can accelerate employee performance improvement. This research is expected to make a theoretical contribution to the literature in this context, certainly in the context of human resource management.